African Growth and Development Policy Modeling Consortium (AGRODEP) - International Food Policy Research Institute (International Food Policy Research Institute, 2010)
AGRODEP seeks to: i) promote access to state-of-the-art economic modeling tools to enable high-quality, locally-based research; ii) facilitate access to existing datasets, improve the quality of such datasets, and raise their local content and relevance; and iii) support collaboration among leading African scientists and their peers outside Africa. AGRODEP provides a set of integrated visualization tools to easily capture and present data from the AGRODEP web portal including Arrow map, bubble map, bubble map with timeline, shaded map, shaded map with timeline. The tools can be embedded anywhere in web sites or can be printed easily.